Hemostatic spray as therapy for pancreatic stump bleeding after cephalic duodenopancreatectomy - Falco, Daniela (2022)
A 70-year-old man with a cholangiocarcinoma underwent a cephalic duodenopancreatectomy. On the 2nd postoperative day, he had hematemesis without hemodynamic instability. Upper endoscopy (EGD) revealed a massive clot at the pancreatic stump, suspected as the source of hemorrhage. After partial clot removal, no active bleeding was found and no therapy was performed. Pancreaticogastric and gastrojejunal anastomoses, as well as the efferent-limb, showed no suspicious lesions. Octreotide was initiated and heparin prophylaxis was temporarily stopped. Bleeding from pancreatic stump following pancreatoduodenectomy is a rare but a life-threatening condition. Conventional endoscopic therapies, including clip placement and cautery, are mostly ineffective and with high risk of pancreatitis. We report the second case of hemostatic powder as a safe and successful therapy in this scenario.